Pemanfaatan Media Visual untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar: Kajian Literatur - Charina Nur Fitriani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Learning interest is an important affective factor because it is closely related to attention, enjoyment, and students' willingness to participate in classroom activities. This article aims to describe the contribution of visual learning media to elementary school students' learning interest. The study employed a structured literature review by examining open-access journal articles published between 2021 and 2025. The selected literature covered static images, interactive video, digital comics, digital presentations, interactive multimedia, and augmented reality. The synthesis shows a consistent pattern: visual media can attract attention and make learning materials easier to understand when the visual elements are relevant to the lesson and accompanied by meaningful learning activities. Interactive video was reported to increase learning interest with an overall N-gain of 0.64, while an experimental study on augmented reality reported a significant difference in learning interest between experimental and control groups (p = 0.042). Other studies indicate that digital comics, images, and interactive presentations support reading interest, motivation, and classroom engagement. These findings suggest that visual media should not be treated merely as decoration. Its effectiveness depends on clarity, relevance, interaction, teacher guidance, and the availability of appropriate learning facilities.